2018
DOI: 10.1103/physrevd.97.076006
|View full text |Cite
|
Sign up to set email alerts
|

Next-to-leading-logarithmic power corrections for N -jettiness subtraction in color-singlet production

Abstract: We present a detailed derivation of the power corrections to the factorization theorem for the 0-jettiness event shape variable T . Our calculation is performed directly in QCD without using the formalism of effective field theory. We analytically calculate the next-to-leading logarithmic power corrections for small T at next-to-leading order in the strong coupling constant, extending previous computations which obtained only the leading-logarithmic power corrections. We address a discrepancy in the literature… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
108
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(112 citation statements)
references
References 45 publications
3
108
1
Order By: Relevance
“…We also showed that requiring a substantially harder jet reduces the effect of power corrections considerably and renders the method more competitive. Our calculation demonstrates the importance of a dedicated program to compute the effects of power corrections analytically, as has already been performed for the color-singlet case [12,36,[39][40][41], in order to improve the effectiveness of the N -jettiness method.…”
Section: Discussionmentioning
confidence: 89%
“…We also showed that requiring a substantially harder jet reduces the effect of power corrections considerably and renders the method more competitive. Our calculation demonstrates the importance of a dedicated program to compute the effects of power corrections analytically, as has already been performed for the color-singlet case [12,36,[39][40][41], in order to improve the effectiveness of the N -jettiness method.…”
Section: Discussionmentioning
confidence: 89%
“…In this section we analyze the terms that contribute to the NLP-NLL cross section. In the color-singlet case, it was observed [6,7] For processes with one jet in the final state, the NLL power correction are inherently process dependent since they require the subleading collinear matrix elements. It is not unreasonable to assume that, like in the color singlet case, there is a choice of ρ i that reduces the impact of power corrections, avoiding the need to implement NLL contributions.…”
Section: F Nlp-nll Contributionsmentioning
confidence: 99%
“…Even if not, elucidation of NLP contributions at a fixed order in α s may have a key role to play in estimating higher order cross-sections. It can furthermore aid in the development of subtraction schemes for the efficient numerical cancellation of infrared singularities [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30], and results using the diagrammatic approach are in progress [51]. The various approaches have also been used to examine NLP effects at fixed order in the coupling [19,20,[52][53][54]. Of particular relevance for the present study is Ref.…”
Section: Introductionmentioning
confidence: 99%